If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -13 = 4x + 5 Reorder the terms: -13 + 5x = 4x + 5 Reorder the terms: -13 + 5x = 5 + 4x Solving -13 + 5x = 5 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -13 + 5x + -4x = 5 + 4x + -4x Combine like terms: 5x + -4x = 1x -13 + 1x = 5 + 4x + -4x Combine like terms: 4x + -4x = 0 -13 + 1x = 5 + 0 -13 + 1x = 5 Add '13' to each side of the equation. -13 + 13 + 1x = 5 + 13 Combine like terms: -13 + 13 = 0 0 + 1x = 5 + 13 1x = 5 + 13 Combine like terms: 5 + 13 = 18 1x = 18 Divide each side by '1'. x = 18 Simplifying x = 18
| 10=16 | | -3(2-3y)=2(1+5y) | | v/2 | | a^3c^2/9b | | x+4=10x-14 | | 4(3x+1)=5x+66 | | .5x+12.3=7.1-1.1x | | 28=3X-14 | | 4(x+x+7)-2x+8-4= | | T^3+8t^2+15t=0 | | 2X^2-7X+3=5 | | (-3-1/3x)^3 | | 2+0.5d=25 | | h=3+80t-16t^2 | | x^2+9=103 | | 5k-21=-3k+24 | | 0.5d-2=25 | | -16p+13p+-1=14 | | 9559=20p+6 | | 22=16t^2+28t+40 | | 6x-6-4x=4 | | 12x+x-17x+6x-8x=-12 | | 4+(3)-2+(6+4*2)= | | -12w+-w+3w-8w=18 | | 20+6=9559 | | m^3+27=0 | | 15p+3p+2p=20 | | (x+3)2=7is | | 5ln(-x+2)=49 | | -(7x-7y-6)= | | 3u+5u-5u+-2u=9 | | (X^2/1.47)-x=0.140 |